1995
DOI: 10.1159/000177886
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phytic Acid and Microbial Phytase on Cd Accumulation, Zn Status, and Apparent Absorption of Ca, P, Mg, Fe, Zn, Cu, and Mn in Growing Rats

Abstract: Three groups of individually housed albino rats (n = 6, initial average weight = 47 g) were fed diets based on egg white and cornstarch (basal diet 8 g Ca, 5.2 g P, 0.76 g Mg, 100 mg Zn, 100 mg Fe, 50 mg Mn, 7 mg Cu, and 5 mg Cd per kilogram diet) over a 4-week period. Group I (controls) was fed the basal diet free of phytic acid (PA) and microbial phytase. In groups II and III cornstarch was replaced by 0.5% PA from NaPA (molar PA/Zn ratio ∼ 5). In group III, 2,000 U of microbial phytase from Aspergillus nige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 16 publications
(17 reference statements)
2
21
0
Order By: Relevance
“…These results show that the high cadmium accumulation in liver and kidneys were due to the sodium phytate added as after phytate degradation by phytases the high cadmium accumulation was reduced [251]. The results were confirmed by the same authors in another rat study, showing also significantly higher cadmium liver and kidney accumulation after application of a sodium phytate containing diets (0.5%) and also a reduction of the accumulated cadmium by supplementation of microbial phytases (2000 U/kg) [252]. A later rat study by Rimbach and Pallauf [253] showed, however, only a slight increase in the cadmium accumulation in the kidneys and no significant alteration of the liver cadmium content with increasing dietary phytate up to 1.4% (3.5 -14.0 g Na -phytate/kg).…”
Section: Phytic Acid Interactions With Toxic Trace Elements (Cd Pb)supporting
confidence: 68%
“…These results show that the high cadmium accumulation in liver and kidneys were due to the sodium phytate added as after phytate degradation by phytases the high cadmium accumulation was reduced [251]. The results were confirmed by the same authors in another rat study, showing also significantly higher cadmium liver and kidney accumulation after application of a sodium phytate containing diets (0.5%) and also a reduction of the accumulated cadmium by supplementation of microbial phytases (2000 U/kg) [252]. A later rat study by Rimbach and Pallauf [253] showed, however, only a slight increase in the cadmium accumulation in the kidneys and no significant alteration of the liver cadmium content with increasing dietary phytate up to 1.4% (3.5 -14.0 g Na -phytate/kg).…”
Section: Phytic Acid Interactions With Toxic Trace Elements (Cd Pb)supporting
confidence: 68%
“…The liver, on the other hand, is rich in free radical scavenging systems, therefore, a reduction in Se may be due to enhanced synthesis of selenoproteins by this organ. The concentrations of the trace elements in the control animals reported in this study are comparable to those reported earlier [19,20].…”
Section: Discussionsupporting
confidence: 91%
“…In contrary to ZN N , PP NH was not an antagonist for ZN I bioavailability in piglets (Analysis II). This finding is in contradiction with the reduced Zn absorbability, Zn status or growth from experiments having studied the effect of supplemental phytate (mostly as sodium phytate, C 6 H 6 Na 12 O 24 P 6 ) in semi-synthetic diets containing or not containing supplemental Zn (O'Dell and Savage, 1960;Oberleas et al, 1962;Rimbach and Pallauf, 1992;Rimbach et al, 1995;Windisch and Kirchgessner, 1999). As phytate from sodium phytate is easily ionizable under a wide pH range, ionized Zn from supplemental sources may rapidly bind to phytic acid (Davies and Nightingale, 1975).…”
Section: Description Of the Databasesmentioning
confidence: 85%